Perbandingan Kontrak Sosial John Locke dan Thomas Hobbes - Adhitya Sandy Wicaksono (UIN Syarif Hidayatullah Jakarta, 2022)
The Social Contract is away so that humans can live a better life and get out of an uncertain natural state, although there are differences of opinion between Thomas Hobbes and John Locke regarding how the social contract should be implemented, both agree that the social contract is the way to peace in which the state will guarantee justice and the welfare of the people. However, both Hobbes and Locke have different views on what the ideal state should look like. Hobbes wanted absolute power and Locke wanted a separation of powers (Trias Politica).